DRIVERS OF ENTREPRENEURIAL GROWTH IN SAUDI ARABIA - Saja Alotaibi, Tahar Tayachi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The rise of entrepreneurship has been phenomenal over the years due to the market demand set by the people. They are now into opening up their own businesses and working even harder to make them work therefore causing rise in the field of entrepreneurship. There are certainly some drivers that promote entrepreneurial growth and these were studied in this work. The aim of this work is to analyze and understand the opportunities created by the entrepreneurial field and why and how did it grow rapidly and to explore the drivers of entrepreneurial growth in the Kingdom of Saudi Arabia (KSA). The methodology used is quantitative methodology, which involves use of survey generated from Google survey. The sample populations of this work were 85 entrepreneurs from Jeddah. The results of the survey showed that the number of entrepreneurs and entrepreneurial firms are increasing. The drivers of entrepreneurial growth in the KSA are education, training, venture capitalists, family and culture as well.